L’intervention comme conception organique : conduite de projet et coopération sociale - Francisco Lima; Francisco Duarte (Activités)
This article presents intervention in ergonomics as an organic design, when, beyond immediate empirical transformations of the material or organizational conditions of work, of changing power relations, the objective of the intervention is to overcome antagonism and competition by developing cooperation and relationships of trust. Based on interventions in the oil industry and in waste collection cooperatives, we put forward a number of reflections on the effectiveness and limits of such interventions. In particular, we highlight: (i) The role of the gatekeeper, watchman or translator between the two worlds, the techno-scientist or experts, and the internal side of the organization; (ii) The external expert’s role in building internal links between watertight functions; (iii) The training of an internal work analysis team as a condition for the appropriation of the methods and for the perpetuation of the engaged movement of change; (iv) design in use, taken into account upstream and downstream of the project; (v) The institutionalization of REX systems as reflective and organizational learning spaces; (vi) The place of activity analysis in the construction of the intervention, its appropriation and its perpetuation.